"An Angry Cow is Not a Good Eating Experience": How US and Spanish media are shifting from crude to camouflaged speciesism in concealing nonhuman perspectives. (2nd April 2016) - Khazaal, Natalie; Almiron, Núria
Abstract : Recent developments in the ideology of speciesism (meaning bias against members of other animal species) within the media deserve analysis. Such discussion is important because speciesism is a major ethical concern. Nonhuman animals suffer massive harm within the industrial farming complex, confined throughout their lives and a high proportion killed while still infants or juveniles. The joint efforts of material institutions, cultural narratives and embodied affects conceal this from the public. As research on this topic is scarce, this study aims to provide tools to improve the quality of journalism regarding ethical issues that concern our relationship with nonhuman animals. We hope to help to formulate an emerging critical animal studies perspective on journalism studies. This article explores the role of news media in constructing perceptions of nonhumans used for food and their treatment. We compare 60 articles from The New York Times (United States) and El País (Spain) over a two-year time frame (2011–2013) using a critical discourse analysis. Our results show that, while both newspapers play a major role in concealing the nonhumans' cruel reality, a distinction can be drawn between the crude speciesism of El País and the camouflaged, more deceptive style of The New York Times .